Family, Friends and Colleagues' Support as Correlates of Job Performance among Non-Teaching Staff of Public Universities in Benue State: Implications for Counselling - Moses Mhide Kpum (Journal of Counseling, Education and Society, 2023)
The study investigated how family, friends and colleagues' support as correlates with job performance of non-teaching staff of public universities in Benue State for counselling implications. The study adopted a correlation research design. The population comprises 2,703 non-teaching staff from three public universities in Benue State: Joseph Sarwuan Tarka University in Makurdi, Benue State University in Makurdi, and the Federal University of Health Sciences in Otukpo. The sample size for the study was 348 non-teaching staff. The sample was selected using proportionate stratified and accidental sampling techniques. The instrument for data collection was a structured questionnaire titled “"Family Support, Friend's Support, and Colleagues' Support, and Job Performance Questionnaire" (FSFSCSJPQ). The questionnaire was validated by experts. The reliability of the questionnaire was established using Cronbach Alpha method which yielded coefficients of 0.81 and 0.84 for sections A and B respectively. Data collected for the study were analyzed using Pearson Product Moment Correlation Coefficient. The study's findings revealed that there is a high positive relationship between family support and job performance of non-teaching staff of public universities in Benue State, and that the relationship was significant. It was also found that, friends’ support and colleagues’ support had a high and significant positive relationship with job performance of non-teaching staff of public universities in Benue State. The study concluded that support networks, including family, friends, and colleagues; significantly contribute to the enhanced job performance of non-teaching staff in public universities in Benue State. Recommendation were made that public universities should organize employee assistance programs and workshops on communication and interpersonal skills using counsellors as facilitators to help build and maintain support networks and public universities in Benue State should establish or expand Counselling services for their non-teaching staff that can address both personal and professional challenges that may affect their job performance.